2013
DOI: 10.1007/s12161-013-9578-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Simple and Rapid Extraction Procedures for the Determination of Pesticide Residues in Fruit Juices by Fast Gas Chromatography–Mass Spectrometry

Abstract: Three sample treatment methods, based on QuEChERS, solid-phase extraction (SPE) and solid-phase microextraction (SPME), were compared and evaluated in order to obtain the best conditions to determine pesticide residues in fruit juice by fast gas chromatography-mass spectrometry (single quadrupole GC-MS). Analysis were performed under selected ion monitoring, acquiring the three most abundant and/or specific ions for each analyte and using their relative intensity ratios as a confirmatory parameter. The 3 metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…The SPME parameters here were selected mainly to meet the needs of practical application of in vivo SPME for apples where salt cannot be added, temperature cannot be changed, and a long extraction time is not preferred. Nevertheless, the parameters were still close to those reported in some references for these commercial fibers [33,37]. The results shown in Figure 3 indicated that the overcoated fiber was infinitely superior to the other fibers.…”
Section: Stability Of Opps In Apple Matrix and Analytical Performancesupporting
confidence: 87%
See 1 more Smart Citation
“…The SPME parameters here were selected mainly to meet the needs of practical application of in vivo SPME for apples where salt cannot be added, temperature cannot be changed, and a long extraction time is not preferred. Nevertheless, the parameters were still close to those reported in some references for these commercial fibers [33,37]. The results shown in Figure 3 indicated that the overcoated fiber was infinitely superior to the other fibers.…”
Section: Stability Of Opps In Apple Matrix and Analytical Performancesupporting
confidence: 87%
“…Up to now, DI-SPME for pesticide residual investigation in apples has been rarely reported. Cherta et al performed DI-SPME in commercial apple juice after dilution with a commercial polyacrylate (PA) fiber [33]. No significant differences or signal enhancements were observed between spiked water and spiked juice samples after 4-fold dilution with deionized water, indicating that commercial apple juice is much less complex than fresh natural apple pulp.…”
Section: Strategies To Ensure the Lifetime Of The Fiber In Apple Matrixmentioning
confidence: 99%
“…Gas chromatography coupled with mass spectrometry is the most commonly applied and established technique for determination of volatile and semi‐volatile analytes of low medium polarity in water and foods. Different types of MS analyzers have been applied for this goal, such as single‐quadrupole, TOF, ion trap and triple quadrupole; however, the two latter can work under tandem MS mode (Cherta, Beltran, Pitarch, & Hernández, ; Hayward, Wong, & Park, ; Lambropoulou, ; Notardonato, Avino, Cinelli, & Russo, ; Ziarrusta, Olivares, Delgado, Zuloaga, & Etxebarria, ).…”
Section: Gc‐tof‐based Methodsmentioning
confidence: 99%
“…Pesticide residues can penetrate into plant tissues and remain in agricultural commodity after they are applied to crops, even after being washed, processed and prepared, and may result in adverse consequences to the human health . As fungicides are widely used in preharvest and postharvest treatments to control fungal diseases of fruits, the residues may appear in processed products such as fruit juices, which are widely consumed . Previous studies reported that fungicides such as azoxystrobin and pyrimethanil could remain in grape products after physicochemical and biological processes and become a significant route of human exposure .…”
Section: Introductionmentioning
confidence: 99%
“…Pesticide residues can penetrate into plant tissues and remain in agricultural commodity after they are applied to crops, even after being washed, processed and prepared, and may result in adverse consequences to the human health [1]. As fungicides are widely used in preharvest and postharvest treatments to control fungal diseases of fruits, the residues may appear in processed products such as fruit juices, which are widely consumed [2,3]. Previous studies reported that fungicides such as azoxystrobin and pyrimethanil could remain in grape products after physicochemical and biological processes and become Abbreviations: BS-ILASEME, binary-solvent-based ionic-liquid-assisted surfactant-enhanced emulsification microextraction; DLLME, dispersive liquid-liquid microextraction; EF, enrichment factor; [HMIM]PF 6 , 1-hexyl-3-methylimidazolium hexafluorophosphate; LDS-LPME, low-density-solvent-based liquid-phase microextraction; UASEME, ultrasound-assisted emulsification microextraction; VASEME, vortex-assisted emulsification microextraction Conflict of interest: The authors declare no potential conflict of interests.…”
Section: Introductionmentioning
confidence: 99%